System of the State Certification of Scientific Personnel of the Higher Qualification in Republic of Belarus - Guennady Vladimirovich Palchik (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article analyzes the system of attestation of scientific and scientific-pedagogical personnel of Higher Attestation Commission of the Republic of Belarus considered it particularly defined priorities and objectives of Higher Attestation Commission of the Republic of Belarus as the republican government authority to regulate relations in this sphere.